Contribution of Digital Branding for Improving Madrasah Tsanawiyah Quality Education’s on the Pantura Area’s of Lamongan - Arif Mansyuri; Achmad Anwar Abidin (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
Discussion in this article is about the importance of madrasahs in utilizing digital media in branding themselves or building a madrasa self-image hammering digital media, especially social media digital platforms which have become a daily necessity of the community. According to researchers, the encouragement of the use of digital media is very necessary because the direction of society at this time is more active in surfing in cyberspace than in the real world, proof that discussions in social media on an issue develop faster than issues that are not blowed-up in digital media. The method used in this discussion is a qualitative method with a multi-site case study approach in three tsanawiyah madrasahs in the pantura kabupten Lamongan area. The results of this study show that the implementation of digital branding strategies in three MTs in Lamongan district has many points of similarity. There are at least two Strategies, namely the first: brand expression through logo, vision, mission, motto and tagline. Both communication brands. The branding communication strategy is to introduce the institution to the external which is displayed digitally on the school's website, school social media, such as facebook, Instagram, twitter and Youtube. All three have branding that is favored differently. MTs Mazrotul Ulum further strengthens the personality of teachers and educators as madrasa ambassadors. while MTs Tarbiyatut Tholabah highlighted his achievements in extracurricular championships. As well as MTs Muhammadiyah 2 Karangasem is self-sufficient with its International Cambridge program